The PsyCourse Infrastructure as an Example for Longitudinal Research in Biological Psychiatry - A. Gryaznova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Both genetic and environmental factors play a major role in the etiology of mental illnesses. Longitudinal studies collecting many phenotypes and biomaterials help to elucidate this complex interplay. PsyCourse is an observational longitudinal multi-center (19 centers) study of severe mental disorders conducted in Germany and Austria, that, to date, collected data from more than 1,500 patients and control individuals. Here, we give an overview of the key properties and, specifically, the infrastructure of the PsyCourse study. Beside the study protocol, we provide information on IT tools, data management, data protection, quality control, data analysis, and data sharing with collaborators. We also highlight the need for fundamental preparation.